The reality of application Department of Education in Jeddah to the standards of the educated organization and its relationship with Institutional Excellence from the point of view of its employees: - Al-Harbi, Dina Mesfer; Al-Abbasi, Dalal Omar (Journal of Educational and Psychological Sciences, 2022)
The aim of the research is to identify the reality of the application of the controls of the educated organization and the achievement of institutional excellence in the management of education in the city of Jeddah and the nature of the relationship between them, from the point of view of its employees, in light of the variables (academic qualification, current job title, current years of experience) To achieve the objectives of the research, the researcher followed the relational quantitative approach, and the questionnaire as a research tool, and it was distributed to a simple random sample of (312) female employees. The search results showed; The first axis: the learning organization obtained an overall average (3.24 out of 5) with a (medium) degree of application, and the averages of the sub-dimensions were; Personal Empowerment (3.35), Team Learning (3.26), Mental Models (3.25) Shared Vision (3.18) and Systematic Thinking (3.14), all with a (medium) degree of application. Achieved (medium) for the seven dimensions of excellence; Their averages were arranged in descending order as follows: Partnerships and Resources (3.43) and a degree of excellence (high), then strategic planning (3.40), beneficiaries results (3.28), key performance results (3.27), administrative leadership (3.26), operations, products and services management (3.23), human resources (3.22) and finally human resources results (3.22), all with a degree of distinction (medium), and the value of Pearson’s correlation parameters between the dimensions of the educated organization’s controls and the dimensions of institutional excellence ranged between (0.70- 0.89) and confirm the existence of a strong and positive correlation with statistical significance, and the presence of statistically significant differences at the level of 0.05 in the degree of Applying the controls of the learning organization and the degree of achieving institutional excellence due to the educational qualification variable in favor of the bachelor, and according to the, current job title in favor of the educational supervisors, and according to the , current years of experience in favor of the most experienced. In light of these results, the researcher recommended the Department of Education in Jeddah; By activating the application of all the controls of the learning organization to achieve institutional excellence in a better degree, and to achieve the requirements of each, and to raise awareness of the importance of these two concepts in all education departments in the Kingdom, in addition to proposals for complementary studies on the subject.
Keywords: relationship; learning organization; institutional excellence; education management; Jeddah city